Chromatin-Associated Protein Sugp2 Involved in mRNA Alternative Splicing During Mouse Spermatogenesis - Zhan, Junfeng; Li, Jianbo; Wu, Yuerong; Wu, Panfeng; Yu, Ziqi; Cui, Peng; Zhou, Mofan; Xu, Yumin; Jin, Tingyu; Du, Ziye; Luo, Mengcheng; Liu, Cong (Frontiers in Veterinary Science, 2021)
Mammalian spermatogenesis is a highly ordered process that is determined by chromatin-associated moderators which still remains poorly understood. Through a multi-control group proteomics strategy, we confirmed Sugp2 was a chromatin-associated candidate protein, and its signal arose along spermatogenesis. The expression results showed that Sugp2, which is mainly expressed in the testis, had two transcripts, encoding one protein. During spermatogenesis, Sugp2 was enriched in the nuclear of male germ cells. With depletion of Sugp2 by CRISPER-Cas9 technology, we found that Sugp2 controlled a network of genes on metal ion and ATP binding, suggesting that alternative splicing regulation by Sugp2 involved in cellular ion and energy metabolism during spermatogenesis. While Sugp2 had little effect on meiotic progression and male fertility. Collectively, these data demonstrated that as a chromatin-associated protein, Sugp2 mediated alternative splicing regulatory network during spermatogenesis.